Pengaruh Belanja Pemerintah dan PDRB terhadap Ketimpangan Pendapatan Provinsi Kaltim Tahun 2014–2023 - Salsabilla Ayu; Prayudi Setiawan Prabowo (Jurnal Ekonomika : INDEPENDEN, 2025)
Income inequality in East Kalimantan Province remains an issue of concern despite the region’s improving economic growth during the period 2014–2023. The increase in Gross Regional Domestic Product (GRDP), largely driven by the mining and oil and gas sectors, has not resulted in an equitable distribution of income across regions. This study aims to analyze the effects of government expenditure on the economic, education, and social protection functions, as well as GRDP, on income inequality at the district and city levels in East Kalimantan Province. The method employed is panel data regression, with model selection conducted using the Chow test, Hausman test, and Lagrange Multiplier test. The results indicate that government expenditure on the economic function significantly reduces income inequality, while expenditure on the education and social protection functions shows a positive and significant association with income inequality. GRDP has a positive effect on income inequality, supporting the view that economic growth in its early stages tends to increase disparities. Simultaneously, all independent variables are found to have a significant effect on income inequality. These findings highlight the importance of improving the effectiveness of public spending and implementing more inclusive fiscal policies to promote a more equitable distribution of welfare in East Kalimantan Province.